Unrecognised Ant Megadiversity in the Australian Monsoonal Tropics III: The Meranoplus ajax Forel Complex - Alan N. Andersen; François Brassard; Benjamin D. Hoffmann (Diversity, 2024)
Australia’s monsoonal (seasonal) tropics are a global centre of ant diversity, but are largely unrecognised as such because the vast majority of its species are undescribed. Here we document another case of undescribed hyper-diversity within a taxon that is formally recognised as a single, widespread species, Meranoplus ajax Forel. We recognise 50 species among 125 specimens of M. ‘ajax’ that we CO1-barcoded, integrating CO1 clustering and divergence, morphological differentiation and geographic distribution. A large proportion (44%) of these species are represented by single records, indicating that very many additional species are yet to be collected in this extremely remote and sparsely populated region. Sampling has been concentrated in the Northern Territory, where 27 of the 50 species occur. If diversity in Western Australia and Queensland were similar to that in the Northern Territory, as appears likely, then the M. ajax complex would comprise >100 species. In 2000, when Australia’s monsoonal ant fauna was estimated to contain 1500 species, Meranoplus ajax was considered to represent a single species. Our previous analyses of a range of other taxa have shown that their diversity has been similarly under-appreciated in this estimate. Our findings suggest that the total number of ant species in monsoonal Australia is several thousand, which would make the region by far the world’s richest known.